2019
DOI: 10.1108/jea-05-2017-0060
|View full text |Cite
|
Sign up to set email alerts
|

Ethical dilemmas in education: a case study of challenges faced by secondary school leaders in Kenya

Abstract: Purpose The purpose of this paper is to question the usefulness of Euro-Western concepts of principled ethical behaviour for school leaders in non-Euro-Western countries by examining the dilemmas faced by Kenyan educational leaders. Design/methodology/approach A single, multi-site case study methodological approach was used, and data gathered by means of semi-structured interviews with stakeholders: school principals, boards of governors, heads of department, school bursars and parents. Findings Findings h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Erdoğan (2019) observed that school directors and teachers face ethical dilemmas at a moderate level, not excessively high or low. Oduol and Cornforth (2019) found that secondary school administrators often encounter ethical dilemmas. Ehrich et al (2011) examined that it is inevitable for teachers, whose professions are primarily based on moral values, to experience ethical dilemmas.…”
Section: Discussionmentioning
confidence: 99%
“…Erdoğan (2019) observed that school directors and teachers face ethical dilemmas at a moderate level, not excessively high or low. Oduol and Cornforth (2019) found that secondary school administrators often encounter ethical dilemmas. Ehrich et al (2011) examined that it is inevitable for teachers, whose professions are primarily based on moral values, to experience ethical dilemmas.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the overlap, unmasking and stimulating indigenous particularities – for example, mutuality and reciprocity – could inspire organic connections between school and communities, allowing teachers to diversify pupils’ experiences in response to their complex social, academic and cultural lives. Conversely, to comply with the new governance regimes that require results-based management (MOE, 2012b; Oduol, 2014) alongside demands for globalization infiltrating through the government–NGO partnership, evidence from the headteacher suggested that the space for infusing aspects of local heritage was narrowing down. While incorporating ideas from global communities may not necessarily be unhelpful, uncritical adoption of globalized ideas has been found to produce unnecessary ethical issues in Kenya (Oduol, 2014) or to lead to more conflicts in post-conflict communities (Davies, 2010).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…These were not only enacted as a ritual, but as a way of ensuring community consensus and committing oneself to community good (Malunga, 2006). However, while such morals were ‘consensually drawn beliefs, standards, and principles about good conduct taken as obligatory’ among all community members (Oduol, 2014: 14), Choti (2009) and Oduol (2014) studies in Kenya reported how political/government interference in schools created ethical dilemmas for school leadership and jeopardized any attempt at inculcating shared principles about good conduct. This implies that when government/political dysfunctionalities infiltrate into schools, school leaders’ quest for community-sensitive practices stands threatened.…”
Section: Kenya School Leadership In Indigenous Contextmentioning
confidence: 99%
“…Other studies indicated that the ethical dilemmas that stemmed from the interests of the school community were particularly complex (Cranston et al, 2006). When the consequences of the ethical decision are likely to effect the whole community and not only one individual, there is greater pressure on the principal (Crawford, 2017; Oduol and Cornforth, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%